Company Profile Application Design as Promotional Media Using Laravel: Case Study in Creative Design Field - Nurhanifah, Hanny; Ibrahim, Rohmat Nur; Kusnandar, Toni; Utami, Alia Tri (P3M, STIE Pasundan, Bandung, Indonesia., 2024)
Keratip Design, a design agency specializing in creative services such as graphic design, encounters intense competition in the expanding design market. Presently, corporations depend on social media as a means of promotion. However, the outcomes could be more optimal. Moreover, Keratip Design encounters challenges in engaging with prospective customers, impeding the company's capacity to establish robust connections with potential clients. In order to address these problems, it is imperative to create and construct a contemporary, engaging, and appealing company profile application utilizing Laravel as the development framework. By utilizing Laravel as the underlying framework for constructing the company profile application, Kereatif Design can enhance the program's performance, bolster its security measures, and facilitate future expansion of its functionality. The app will allow Keratip Design to effectively showcase its portfolio, outline its design services, and furnish clients with the company's contact information in an immersive and dynamic manner. This project aims to develop a corporate profile application utilizing Laravel as a promotional instrument for Keratip Design. By utilizing this program, Keratip Design aims to enhance its online presence, attract prospective consumers, and improve user experience. This study's results can significantly enhance a company's visibility, enhance company reporting, foster more substantial engagement with potential consumers, and enhance presentations.